The end of the world Apocalypse and its aftermath in Western culture - Lisboa, Maria Manuel, 1963-; Open Book Publishers (Open Book Publishers, 2011)
"Our fear of the world ending, like our fear of the dark, is ancient, deep-seated and perennial. It crosses boundaries of space and time, recurs in all human communities and finds expression in every aspect of cultural production - from pre-historic cave paintings to high-tech computer games. This book examines historical and imaginary scenarios of Apocalypse, the depiction of its likely triggers, and imagined landscapesin the aftermath of global destruction. Its discussion moves effortlessly from classic novels including Aldous Huxley's Brave New World, George Orwell's Nineteen Eighty-Four and Margaret Atwood's Oryx and Crake, to blockbuster films such as Blade Runner, Armageddon and The Terminator. The author also takes into account religious doctrine, scientific research and the visual arts to create a penetrating, multi-disciplinary study that provides profound insight into one of Western culture's darkest and most enduring preoccupations."--Publisher's website.
Prologue -- 1. Apocalypse now and again -- 2. The world gone M.A.D. -- 3. And then there was nothing: is the end ever really the end? -- 4. Falling out with Hal and Hester -- 5. Dying of happiness: Utopia at the end of this world -- Afterword: Libera me, Domine, de vita æterna.
Available through Open Book Publishers.
Includes bibliography (pages 177-186) and index.
Mode of access: World Wide Web.
Keywords: Apocalypse in art; Apocalypse in literature; Apocalypse in motion pictures; Apocalytpic literature -- History and criticism; End of the world in literature